Using Blended and Virtual Schwartz Center RoundsÂ® to Support Maternity Staff in Ireland During the Covid-19 Pandemic - Doherty, Jean; Devine, Clara K; Cullen, Sarah (Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: Many staff supports, such as the internationally accredited Schwartz Center Rounds were suspended worldwide during the Covid-19 restrictions, at a time when they were most needed. Schwartz Rounds are multi-disciplinary forums where staff can discuss the emotional, social and ethical challenges of care in a confidential and safe environment, intending to improve staff well-being and patient care. In a bid to improve staff support after the suspension of full Schwartz Rounds, virtual, then blended (limited spaces for socially distanced in-person attendance and virtual access) Rounds were initiated.Purpose: This study aimed to evaluate Schwartz Rounds in a maternity setting in Ireland and compare full-in person Rounds with virtual and blended Rounds.Methods: Standard Schwartz Rounds evaluation forms were completed by Rounds attendees. Data were analysed using SPSS (Version 24). Respondents were invited to include a comment at the end of the form, and these free-text comments were analysed thematically.Results: Six Rounds were evaluated (2 full in-person Rounds attended before the pandemic, 1 virtual, 3 blended) and a total of 115 evaluation forms were completed. The Rounds were rated extremely high. Some, but not all aspects of the Rounds were rated more positively from the full in-person Rounds. Some technical difficulties were a barrier to fully experiencing the Round when attending remotely.Conclusion: Schwartz Rounds are attended by staff in over 560 healthcare organisations, internationally and have been reported to improve staff well-being and teamwork. The pandemic saw Schwartz Rounds being suspended in most organisations due to social distancing guidelines. Virtual and blended Rounds are recommended as an effective replacement for full Schwartz Rounds while social distancing and infection control measures are in place. However, in order to improve post-panellist discussion and gain the full Schwartz Round experience, recommencement of full, in-person Rounds are recommended as soon as public health measures allow